Studi Profil Literasi Sains Siswa dan Pembelajarannya di SMP Kota Banda Aceh - Fadil Fitra Kamil; Anna Permanasari*; Riandi Riandi (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
Descriptive research on the study of the scientific literacy profile of students and their learning at SMP Kota Banda Aceh, aims to examine the extent to which aspects of scientific literacy according to PISA 2018 are internalized in the junior high school science learning process. In addition, this study also examines its impact on students' scientific literacy. Research data to reveal the emergence of aspects of scientific literacy in planning learning, implementation of learning, and evaluation of learning for junior high school students in Banda Aceh on science subjects. collected through an instrument that refers to the 2015 Program for International Student Assessment (PISA) framework. The data collection technique was carried out through observation, surveys, and content analysis. The research participants involved 9 junior high schools from 9 sub-districts throughout the city of Banda Aceh, each sub-district selected 1 school. The total participants involved were 135 students. The results showed that for the Planning component, the Knowledge Aspect was presented at the largest 35.9% but the aspect that was dominated by the competence aspect for indicators explained the phenomenon scientifically. In the Implementation component, the largest 44.8% of the Knowledge Aspect is presented and it is also dominated by the knowledge aspect for the epistemic knowledge indicator. In the Evaluation component, the Context Aspect is presented at 41.2% which is dominated by the competence aspect for indicators of interpreting scientific data and evidence. The scientific literacy profile in answering the 2015 PISA questions only 1.48% of students were able to answer up to level 2. This shows that the scientific literacy profile of Banda Aceh Junior High School students is still relatively low. The practice of learning science does not contribute much to the achievement of scientific literacy for junior high school students in Banda Aceh